Unleashing Justice’s Future: The Dawn of Neuro-Cognitive Risk Assessments (NCRA) in Transforming Rehabilitation - Mulyadi, Mahmud; Fernando, Zico Junius; Putra, Panca Sarjana; Anditya, Ariesta Wibisono (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
Neuro-Cognitive Risk Assessments (NCRA) represent a groundbreaking innovation in the criminal justice system, concentrating on evaluating cognitive and decision-making factors to assess inmate recidivism risk. Introduced initially in Houston, Texas, in 2017, NCRA have shown substantial efficacy, evidenced by a 2020 study reporting an Area Under the Curve (AUC) value of 0.70, signifying a significant advancement in recidivism prediction. This research employs normative legal methods, utilizing a conceptual, comparative, and forward-looking approach, characterized as descriptive-prescriptive with data analyzed through content analysis. Key advantages of NCRA include their emphasis on cognitive factors and their capability to operate independently via digital platforms, reducing bias and enhancing objectivity. The global adoption of NCRA, including in countries like Canada, the Netherlands, and Australia, underscores its recognition as a promising tool in criminal justice practices. However, ethical considerations and responsible usage are paramount, ensuring the protection of individual rights and involving diverse stakeholders. The integration of NCRA into rehabilitation programs and public policies presents opportunities to enhance efforts against recidivism. By identifying individual needs more accurately and improving predictions of rehabilitation success, NCRA can motivate inmate engagement in rehabilitation initiatives. Moreover, NCRA support the development of effective crime prevention policies, contributing to broader societal well-being. In conclusion, NCRA represent a transformative approach in criminal justice, leveraging cognitive assessments to refine recidivism risk evaluations and enhance rehabilitation outcomes. Ethical deployment and collaborative engagement are critical to maximizing NCRA's potential in promoting justice and reducing reoffending globally.